Martabat Tujuh in Indigenous Diplomacy: Reconstructing Buton’s Hierarchical Communication System for Contemporary Conflict Resolution - La Ode Muhammad Alfian Zaadi; Nurhayati Nurhayati (Jurnal Ragam Pengabdian, 2026)
Martabat Tujuh, the 17th-century customary constitution of the Buton Sultanate in Southeast Sulawesi, Indonesia, represented a unique integration of Islamic metaphysics and indigenous political culture. While its legal authority ended after national unification, its governance philosophy continues to operate through the living moral code of Binci Binciki Kuli, particularly in indigenous conflict resolution practices. This study reconstructs Martabat Tujuh as a hierarchical communication system and examines its contemporary relevance for diplomacy and peacebuilding. A qualitative design integrating ethnography of communication and hermeneutics was applied, with data collected from customary leaders through interviews, Baruga observations, and document analysis. Findings reveal a multi-tiered mediation process rooted in relational ethics moving from Parabela to Bonto, Kenepulu, Sapati, and only exceptionally to the Sultan. Baruga serves as a deliberative space uniting rational persuasion and spiritual accountability. This study identifies Martabat Tujuh as an indigenous theoretical foundation for communicative governance in modern Indonesia.